THE ABSENCE OF UNILATERAL PATELLA IN A 7-YEAR-OLD BOY: A RARE CASE REPORT - Anggia, Amelia; Yueniwati, Yuyun (Department of Radiology, Medical Faculty, University of Brawijaya, 2026)
Given its rarity, congenital patellar agenesis is seldom encountered in clinical practice, and its presentation is sparsely recorded in existing studies. Due to the condition does not often occur by itself and is more often seen with larger genetic syndromic constructs, reporting on the exact condition prevalence is still a challenge, considering the almost non-existent number of cases documented on the global reporting level. A 7-year-old boy presented with a chief complaint of non-straightening of the right knee since birth. His right knee was hyperflexed, and he had to walk with the help of a walker. The patient had undergone knee surgery to reduce the bending, but there was no improvement. The radiograph showed no patellar bone on the right knee. Knee MRI revealed superior malposition of the right patellar bone to the distal 1/3 of the anterior femur region. Findings also show a ±114° flexion contracture of the right knee, atrophy of the right patellar tendon, and hypotrophy of the m. quadratus femoris. The patient underwent contracture release with an improvement in extension ability. The importance of rapidly and accurately diagnosing foot deformities is critical to reducing morbidity and improving the quality of life of affected individuals, as well as interventions in similar cases. Therefore, radiologists play an important role in diagnosis and treatment planning in unilateral congenital patella absence.